Phase transition and volume expansion in CO2-expanded liquid systems - Denardin, F.; Vieira De Melo, S.; Mammucari, R.; Foster, Neil (2013)
Binary mixtures of conventional solvents are very useful in the dense gas processing of pharmaceuticals. However, the lack of experimental data for ternary systems of organic solvents and dense carbon dioxide hinders the full exploitation of solvent engineering for particle formation by dense gas processing. In this work, volume expansion and mixture critical points for binary and ternary systems of organic solvents and carbon dioxide were experimentally determined at different temperatures and pressures. Results show an exponential behavior of the liquid volume expansion with pressure as the mixture come close to the mixture critical point. Copyright © 2013, AIDIC Servizi S.r.l.